The Twenty-Sixth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2007)

Ethical Guidelines Handbook for the Catholic Laity in Apostolic Service - The English Speaking Catholic Council (ESCC) (2007)

Reasonable Accommodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)
We agree with the Commission that “the management of diversity, especially religious diversity... appears above all to pose a problem.” The appearance of a problem seems to have been provoked in large measure by post 9/11 “alarmist media coverage.” Careful reflection will show that there is no problem in reality and that the alarm is not worthy of Quebecers. The ESCC therefore counsels strongly against the temptation to tamper with the current constellation of relevant rights and privileges in Quebec; it is a product of the unique evolution of Quebec society and functions well as “a fair, original model of collective life of which we are proud.”

Accommodements raisonnables et liberté de religion au Québec - The English Speaking Catholic Council (ESCC) (2007)
We agree with the Commission that “the management of diversity, especially religious diversity... appears above all to pose a problem.” The appearance of a problem seems to have been provoked in large measure by post 9/11 “alarmist media coverage.” Careful reflection will show that there is no problem in reality and that the alarm is not worthy of Quebecers. The ESCC therefore counsels strongly against the temptation to tamper with the current constellation of relevant rights and privileges in Quebec; it is a product of the unique evolution of Quebec society and functions well as “a fair, original model of collective life of which we are proud.”